DEALING WITH INSULIN RESISTANCE AMONG WOMEN WITH POLYCYSTIC OVARIAN SYNDROME - AZIZ, U; AFZAL, M; YOUSAF , RT; IMRAN , S; SARFRAZ, T; JAVED, HR; SULTAN, W (Biological and Clinical Sciences Research Journal, 2023)
One of the most prevalent endocrine disorders in females, polycystic ovarian syndrome (PCOS), affects about 7-8% of women of reproductive age. Most females with PCOS also have increased cholesterol levels, insulin resistance, and BMI, leading to obesity. The study aimed to determine the effects of metformin and lifestyle modification (diet & exercise) on insulin resistance secondary to PCOS after 6 months of use. This RCT study was conducted at Arif Memorial Teaching Hospital from October 2022 to March 2023. The study compared the effects of metformin and lifestyle management, including only a diet plan with the use of metformin diet and exercise plan, on insulin resistance in 130 obese females aged between 20-40 years suffering from PCOS and had insulin resistance as diagnosed by HBA1C blood test. The main outcome measure was the reduction in the HBA1C level. The 130 participants were equally divided into two groups. Group A received metformin only, while Group B received metformin and an exercise plan. Baseline treatment included guidance to adopt a healthy diet. The results showed significant improvement in HBA1C level (P=0.00), BMI (P=0.02), and pregnancy rate. There was an overall improvement in the menstrual pattern but a significant improvement in Group B (P=0.00) than Group A (P=0.06). With a significant rise in follicle-stimulating hormone (FSH) levels in both groups [P=0.06 (A), P=0.01(B)], a statistically significant decrease in luteinizing hormone (LH) [P=0.02 (A), P=0.01(B)] was seen. A total drop in free testosterone level was also seen, but it wasn't significant [P=0.08 (A), P=0.06 (B)]. The study concluded that insulin resistance could be controlled effectively by acquiring a healthy lifestyle, including high protein and low carb, caloric deficient diet, and following an exercise plan and pharmacological treatment. Combining all three treatment options is more effective than using any one option as treatment.